"A Trust That Cannot Be Delegated": The Invention of Ratification Referenda. Issue 4 (20th November 2015) - LENOWITZ, JEFFREY A.
Abstract : A ratification referendum is a procedure in which framers submit a constitution to the people for binding approval before implementation. It is widespread, recommended, and affects the contents and reception of constitutions, yet remains unstudied. Moreover, the reasons or justification for using the procedure remain unexplored. This is troubling because ratification referenda are optional, and thus should only be implemented for good reasons that, today, are no longer given. This article begins correcting this oversight by identifying those that brought about the first ratification referendum and explaining why they did so. I demonstrate that the Berkshire Constitutionalists called for the procedure during the events leading up to the creation of the 1780 Massachusetts Constitution, and that they justified their actions by asserting that the people have an unalienable right to ratify their constitution through a referendum, for this provided needed protection against potentially corrupt elites. This argument remains the most fully developed justification for the procedure to date. My analysis not only reveals ratification referenda to be another product of early American political thought, but also points the way forward for future evaluation of the procedure, and forces reflection upon the importance of having solid grounds for the choices involved in structuring a constitution-making process.